Analysis of Risk Factors for Stunting Among Toddlers Aged 24-59 Months in the Working Area of Cibodasari Puskesmas Community Health Center, Tangerang City - M. Ilham; Rina Amelia (Trigin Institute, 2024)
This research investigates risk factors for stunting among toddlers aged 24-59 months in the working area of the Cibodasari Puskesmas Community Health Center in Tangerang City. Stunting, defined as height-for-age z-scores (HAZ) below -2 standard deviations from the median of the WHO Child Growth Standards, remains a significant public health concern in Indonesia, impacting child health and development. Through a cross-sectional study design, data were collected on maternal and child characteristics, household socio-economic status, feeding practices, access to healthcare services, and environmental factors. Statistical analyses, including bivariate and multivariable regression analyses, were conducted to identify risk factors associated with stunting prevalence. Key findings reveal a high prevalence of stunting among toddlers in the study population, with significant associations observed with maternal nutrition, household socio-economic status, feeding practices, access to healthcare services, and environmental factors. The implications of the findings for public health policies and interventions are discussed, emphasizing the importance of multi-sectoral approaches, early intervention strategies, socio-economic empowerment, enhanced healthcare access, environmental health interventions, and community engagement efforts in reducing stunting prevalence and improving child health outcomes within the community. These findings contribute valuable evidence to inform targeted interventions aimed at addressing the root causes of stunting and promoting child health and well-being in Tangerang City.